Brain Structural and Perfusion Signature of Amyotrophic Lateral Sclerosis With Varying Levels of Cognitive Deficit - Shen, Dongchao; Hou, Bo; Xu, Yinyan; Cui, Bo; Peng, Pan; Li, Xiaolu; Tai, Hongfei; Zhang, Kang; Liu, Shuangwu; Fu, Hanhui; Gao, Jing; Liu, Mingsheng; et al. (Frontiers in Neurology, 2018)
Objective: To characterize the patterns of brain atrophy and perfusion as measured by arterial spin labeling (ASL)-MRI, in amyotrophic lateral sclerosis (ALS) patients with varying levels of cognitive deficit, including ALS with frontotemporal dementia (FTD). Methods: A total of 55 ALS patients and 20 healthy controls (HCs) were included, and all participants underwent neuropsychological assessments and MRI scans. According to their cognitive performance, ALS patients were further subclassified into ALS with normal cognition (ALS-Cn, n=27), ALS with cognitive impairment (ALS-Ci, n=17), and ALS-FTD (n=11). Voxel-based comparisons of grey matter (GM) changes and cerebral blood flow (CBF) were conducted among the subgroups. Results: The whole-brain comparisons of GM changes and CBF among ALS-Ci, ALS-Cn, and HCs were not significantly different. However, the ALS-FTD patients demonstrated a similar pattern of GM loss and hypoperfusion with more significant alterations in the left frontal and temporal lobe compared to the HCs, ALS-Cn and ALS-Ci patients. Decreased CBF was found in many of the same brain areas wherein structural alterations occurred, although isolated GM loss and hypoperfusion were also observed. Additionally, for both GM and CBF abnormalities, a similar pattern of changes was found in the comparisons of ALS-FTD vs. ALS-Ci, ALS-FTD vs. ALS-Cn, and ALS-FTD vs. HCs, with the differences being most significant between ALS-FTD and HCs. Conclusion: The cognitive status of ALS patients is associated with different patterns of GM changes and cerebral perfusion. ASL-MRI might be a useful tool with which to investigate the pathological burden of ALS and to disclose the early signature of possible cognitive impairment.